Lupin, Lupinus L. - Cowling, Wallace A.; Buirchell, B.J.; Tapia, M.E.; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1998)
This monograph focuses on the Mediterranean lupin species and one South American species (L. mutabilis). These species have relatively large seeds and some of them have already been domesticated and have become established crops. Constraints to the use of lupin worldwide are considered, as is the use of the largely untapped genetic diversity that is available in lupin collections. An attempt is made to summarize the major international lupin collections and to identify the major gaps in lupin genetic resource collections. Information is presented under the following main headings: taxonomy and common names; botanical description (including cultivated lupins of the Old and New Worlds and wild lupins of the Old World of potential agricultural significance); origin and centres of diversity; nutritional value and uses; genetic resources; lupin breeding; production and agronomy; and prospects, limitations and priorities. (Abstract © CAB ABSTRACTS, CAB International)